The temptation of Jesus and other sermons - Eyton, Robert (London, UK Kegan Paul, Trench, Trubner and co., 1899)
Includes biblioographical references.
Donated by Mr R.C. Croucher.
Keywords: Jesus Christ -- temptation -- addresses, essays, lectures